ANALISIS MODEL QUALITY VALUE: PERSEPSI PENGHUNI PERUMAHAN - Fety Nurlia Muzayanah; Rediawan Miharja; Agustifa Zea Tazliqoh; Sherly Agustin; Nur Rapina (Eqien - Jurnal Ekonomi dan Bisnis, 2026)
This study pertains to the enhancement of understanding about the Quality Value Model, particularly concerning the strategic national issue of housing construction for the populace of Indonesia. The literature indicates that quality management science has been addressed in several prior research; nevertheless, it has not yielded complete insights specifically pertaining to the perception of quality, particularly from the perspective of housing users. The Indonesian populace badly requires this strategic housing initiative. Indonesia is presently experiencing a housing ownership dilemma. The elevated demand for housing has prompted the housing sector to expand and intensify competition among developers. This work aims to generate supplementary scientific references through a conceptual Quality Value model, serving as a complete strategy to elucidate current dynamics and foresee new challenges. This study employs a quantitative methodology. This research employs PLS-SEM as the analytical tool. The results of this research consist of a mapping of the Quality Value model. This research has two implications. The initial aspect is scientific, represented by a new reference from the Quality Value model on housing occupant perceptions. The second pertains to a reference or practical strategic consideration for stakeholders of the National Strategic Program: Housing Occupant Perceptions.